(untitled) (Kriminalističke teme, 2017)
Reason for writing and research problem(s): Privatization of security started in Serbia in 1990s when first private security companies were established. Besides taking care of people and property in regular circumstances they have to perform security task also during emergencies and disasters. Private security guards have always been on the first line when we speak about these kind of situatiuon. Their first task- protection of property, people and business, they oftenly fulfill together with Sector for emergency management, police, military and other state actors and actors from civil society sector (Red Cross, Mountain Rescue Service etc.). In this article, the authors made an critical oversight of private security in Serbia today and they tryed to explain its important role in complex processes of managing risks in protecting property, people and business. aims of the paper (scientific and/or social): Scientific aim of the article is to introduce notion “policing” to Serbian security vocabulary since it is more propriate to cover all activities of the various social subjects directed to prevent crime and other social de- viations. The aim was also to pay attention of the researchers and experts to important role of the private security in prevention and risk management. Methodology/ Design: Attitudes presented in this article are mostly emerged from the content analysis that we used. Research/ paper limitations: There are two main limitation in preparing this article; (1) inadequat research data base on risk management praxis in Serbian corporations and other szstems and; (2) incomplete licensing system for companies and employees, since that process is still in progress. Results/ Findings: As a system of knowledge and skills, paralelly with growth of professionalization of private security, risk management has been well developed since 2000. But, the praxis of these two is not enough developed. General Conclusion: Reasons for low level of praxis development we can find in relatively low level of “security culture” especially among ruling layer in corporation (especially those which are not private), although the voluntarism is also present in way of managing business in Serbia nowdays. On the other side, although the private security is present in so meny companies, it is not enough involved in preventing and solving/ managing risks. Research/ Paper Validity: Great values, both material and human, are exposed to serious and always new risks that contemporary society and modern lifestyles produce. Scientific research on risk management and the role of a private security sector that counts the same number of members as the police, can best detect problems, bids scientific solutions and functionalize them in the practice of prevention and risk management.